Innovation in the multinational firm with globally dispersed r&d: Technological knowledge utilization and accumulation - Ensign, Prescott C. (Université d'Ottawa | University of Ottawa, 2000)
This paper employs evolutionary, resource-based, and knowledge-based perspectives to provide a framework for understanding technological knowledge sharing within the globally dispersed R&D function of the multinational firm. Elements from the three perspectives are inspected and drawn together. The constructs—knowledge, knowledge transaction, and performance—are articulated. Finally, two fundamental relationships are proposed: (1) kind of technological knowledge shared will impact the type of knowledge transaction undertaken and 2) type of knowledge transaction will impact R&D task performance.